Rapamycin preserves primordial follicles during closed‑system vitrification of mouse ovarian tissue - Yuji Tanaka; Akie Takebayashi; Mari Deguchi; Tsukuru Amano; Akiko Nakamura; Ayako Inatomi; Shunichiro Tsuji; Takashi Murakami (Clinical and Experimental Reproductive Medicine, 2026)
Objective: Ovarian tissue cryopreservation is an essential fertility preservation technique. Two primary methods are used for ovarian tissue cryopreservation: slow freezing and vitrification. Recently, vitrification has been favored over slow freezing, and a closed system is recommended to prevent cross-contamination in liquid nitrogen. Follicular loss during freezing and thawing remains a major challenge. We investigated whether rapamycin, an inhibitor of the mechanistic target of rapamycin (mTOR) pathway, could mitigate primordial follicle loss during closed-system vitrification and thawing of mouse ovarian tissue.Methods: Mouse ovaries were vitrified and thawed with or without 750 nanomolar rapamycin, then immediately analyzed or cultured for 5 days. Activation of the mTOR pathway was assessed using phosphorylated S6 kinase immunostaining, and follicle survival and development were evaluated by histological analysis.Results: Closed-system vitrification did not induce apoptosis in primordial follicles. The median phosphorylated S6K-positive rate in primordial follicles was 7.1% in fresh controls, 87.9% in the rapamycin-free group, and 19.0% in the rapamycin-treated group (fresh-control vs. rapamycin-free and rapamycin-free vs. rapamycin-treated, both p